Rejuvenation of RBCs: validation of a manufacturing method suitable for clinical use. Issue 9 (11th July 2019) - Smethurst, Peter A.; Jolley, Jennifer; Braund, Rebecca; Proffitt, Sue; Lynes, Thomas; Hazell, Matthew; Mellor, Phil; Ridgwell, Kay; Procter, Simon; Griffiths, Alexandra; Marinaki, Anthony M.; New, Helen V.; et al.
Abstract : BACKGROUND: Rejuvenation of stored red blood cells (RBCs) increases levels of adenosine 5′‐triphosphate (ATP) and 2, 3‐diphosphoglycerate (2, 3‐DPG) to those of fresh cells. This study aimed to optimize and validate the US‐approved process to a UK setting for manufacture and issue of rejuvenated RBCs for a multicenter randomized controlled clinical trial in cardiac surgery. STUDY DESIGN AND METHODS: Rejuvenation of leukoreduced RBC units involved adding a solution containing pyruvate, inosine, phosphate, and adenine (Rejuvesol, Zimmer Biomet), warming at 37°C for 60 minutes, then "manual" washing with saline adenine glucose mannitol solution. A laboratory study was conducted on six pools of ABO/D‐matched units made the day after donation. On Days 7, 21, and 28 of 4 ± 2°C storage, one unit per pool was rejuvenated and measured over 96 hours for volume, hematocrit, hemolysis, ATP, 2, 3‐DPG, supernatant potassium, lactate, and purines added (inosine) or produced (hypoxanthine) by rejuvenation. Subsequently, an operational validation (two phases of 32 units each) was undertaken, with results from the first informing a trial component specification applied to the second. Rejuvenation effects were also tested on crossmatch reactivity and RBC antigen profiles. RESULTS: Rejuvenation raised 2, 3‐DPG to, and ATP above, levels of fresh cells. The final component had potassium and hemolysis values below those of standard storage Days 7 and 21, respectively, containing 1.2% exogenous inosine and 500 to 1900 μmoles/unit of hypoxanthine. The second operational validation met compliance to the trial component specification. Rejuvenation did not adversely affect crossmatch reactivity or RBC antigen profiles. CONCLUSION: The validated rejuvenation process operates within defined quality limits, preserving RBC immunophenotypes, enabling manufacture for clinical trials.